2023
DOI: 10.3389/fpubh.2023.1138380
|View full text |Cite
|
Sign up to set email alerts
|

Educational degree differences in the association between work stress and depression among Chinese healthcare workers: Job satisfaction and sleep quality as the mediators

Abstract: BackgroundDepressive status of medical personnel worldwide and especially in China is an important public health and social problem. There is a strong relationship between education and depression, but no studies have studied grouping healthcare workers (HCWs) with different educational degree to discuss whether there are differences in the factors that affect depression. This study aims to examine the role of job satisfaction and sleep quality in the relationship between work stress and depression among Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The investment in healthcare resources, such as doctors and hospital bed, requires a lengthy process. For instance, doctors typically have higher educational levels compared to other professions [ 54 ], and their training period is often prolonged [ 55 ]. Therefore, the long-term convergence rate of investment in healthcare resources is higher than the short-term convergence rate.…”
Section: Discussionmentioning
confidence: 99%
“…The investment in healthcare resources, such as doctors and hospital bed, requires a lengthy process. For instance, doctors typically have higher educational levels compared to other professions [ 54 ], and their training period is often prolonged [ 55 ]. Therefore, the long-term convergence rate of investment in healthcare resources is higher than the short-term convergence rate.…”
Section: Discussionmentioning
confidence: 99%
“…Stress at work has a negative impact on sleep quality [ 53 ]. A two-year follow-up study of healthcare workers also showed that stress levels increased and sleep quality worsened during the pandemic [ 54 ].…”
Section: Discussionmentioning
confidence: 99%